Current and Emerging Technologies for Probing Molecular Signatures of Traumatic Brain Injury - Ercole, Ari; Magnoni, Sandra; Vegliante, Gloria; Pastorelli, Roberta; Surmacki, Jakub; Bohndiek, Sarah Elizabeth; Zanier, Elisa R. (Frontiers in Neurology, 2017)
Traumatic brain injury (TBI) is understood to be an interplay between the initial injury, subsequent secondary injuries and a complex host response all of which are highly heterogeneous. An understanding of the underlying biology suggests a number of windows where mechanistically inspired interventions could be targeted. Unfortunately, biologically plausible therapies have to-date failed to translate into clinical practice. Whilst a number of stereotypical pathways are now understood to be involved, it is not yet possible to characterise the biological phenotype in a truly mechanistically meaningful way, as current clinical characterisation is too crude. In this review, we examine current and emerging technologies for fuller biochemical characterisation by the measurement of multiple and diverse biomarkers simultaneously. We describe how clinically available techniques such as cerebral microdialysis can be leveraged to give mechanistic insights into TBI pathobiology and how multiplex proteomic and metabolomic techniques can give a more complete description of the underlying biology. We also describe spatially-resolved label-free multiplex techniques capable of probing structural differences in chemical signatures. Finally, we touch on the bioinformatics challenges that result from the acquisition of such large amounts of chemical data in the search for a more mechanistically complete description of the TBI phenotype.